Augmented Oscillations in QT Interval Duration Predict Mortality Post Myocardial Infarction Independent of Heart Rate - El-Hamad, Fatima J.; Bonabi, Safa Y.; Müller, Alexander; Steger, Alexander; Schmidt, Georg; Baumert, Mathias (Frontiers in Physiology, 2020)
Objective: This study seeks to decompose QT variability (QTV) into physiological sources and assess their role for risk stratification in patients post myocardial infarction (MI). We hypothesize that the magnitude of QTV that cannot be explained by heart rate or respiration carries important prognostic information. Background: Elevated beat-to-beat QTV is predictive of cardiac mortality, but the underlying mechanisms and hence, its interpretation remains opaque. Methods: We decomposed QTV of 895 patients post MI into contributions by heart rate, respiration and unexplained sources. Results: Cox proportional hazard analysis demonstrates that augmented oscillations in QTV and their level of dissociation from heart rate predict 5-year mortality rate (18.4% vs 4.7%, p < 0.0001) for patients who had no or only one QTV risk predictor. In patients with left ventricular ejection fraction (LVEF) > 35%, the QTV risk score was associated with a significantly higher 5-year mortality rate (16% vs. 4%, p < 0.0001). In patients with a GRACE score ≥120, the QTV risk score was associated with a significantly higher 5-year mortality (25% vs. 11%, p <0.001). Conclusions: Augmented oscillations in QTV and discordance from heart rate, possibly indicative of excessive sympathetic outflow to the ventricular myocardium, predict high risk in patients post MI independent from established risk factors.